Effects of Organic Phosphorus on Methylotrophic Methanogenesis in Coastal Lagoon Sediments With Seagrass (Zostera marina) Colonization - Zheng, Shiling; Wang, Bingchen; Xu, Gang; Liu, Fanghua (Frontiers in Microbiology, 2020)
Methanogens are the major contributors of greenhouse gas methane and play significant roles in the degradation and transformation of organic matter. These organisms are particularly abundant in Swan Lake, which is a shallow lagoon located in Rongcheng Bay, Yellow Sea, northern China, where eutrophication from overfertilization commonly results in anoxic environments. High organic phosphorus content is a key component of the total phosphorus in Swan Lake and is possibly a key factor affecting the eutrophication and carbon and nitrogen cycling in Swan Lake. The effects of organic phosphorus on eutrophication have been well-studied with respect to bacteria, such as cyanobacteria, unlike the effects of organic phosphorus on methanogenesis. In this study, different sediment layer samples of seagrass-vegetated and unvegetated areas in Swan Lake were investigated to understand the effects of organic phosphorus on methylotrophic methanogenesis. The results showed that phytate phosphorus significantly promoted methane production in the deepest sediment layer of vegetated regions but suppressed it in unvegetated regions. Amplicon sequencing revealed that methylotrophic Methanococcoides actively dominated in all enrichment samples from both regions with additions of trimethylamine or phytate phosphorus, whereas methylotrophic Methanolobus and Methanosarcina predominated in the enrichments obtained from vegetated and unvegetated sediments, respectively. These results prompted further study of the effects of phytate phosphorus on two methanogen isolates, Methanolobus psychrophilus, a type strain, Methanosarcina mazei, an isolate from Swan Lake sediments. Cultivation experiments showed that phytate phosphorus could inhibit methane production by M. psychrophilus but promote methane production by M. mazei. These culture-based studies revealed the effects of organic phosphorus on methylotrophic methanogenesis in coastal lagoon sediments and improves our understanding of the mechanisms of organic carbon cycling leading to methanogenesis mediated by organic phosphorus dynamics in coastal wetlands.